2008
DOI: 10.1016/j.jmacro.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Long-run relationships between labor and capital: Indirect evidence on the elasticity of substitution

Abstract: This paper suggests an indirect method for making inference on the parameter region of the elasticity of substitution between capital and labor. The idea is to investigate if the observed behavior of the data is consistent with theoretical relationships that depend on the particular parameter region of the elasticity of substitution. The advantage of this approach is that it allows for more data oriented modeling. Long-run empirical relationships, consistent with a modeling approach for the economy that assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The DICE model uses a Cobb-Douglas production function where the elasticity of substitution between labor and capital equals one. Recent works have criticized the use of the Cobb-Douglas function, and provide empirical evidence that the elasticity of substitution between labor and capital is substantially lower than one (Antras 2004;Chirinko 2008;Juselius 2008;Smith 2008;Chirinko and Mallick 2017). Using a substitution elasticity smaller than one will have three major implications: First, it allows studying the differential impact of factor-specific climate damages on production.…”
Section: The Numerical Modelmentioning
confidence: 99%
“…The DICE model uses a Cobb-Douglas production function where the elasticity of substitution between labor and capital equals one. Recent works have criticized the use of the Cobb-Douglas function, and provide empirical evidence that the elasticity of substitution between labor and capital is substantially lower than one (Antras 2004;Chirinko 2008;Juselius 2008;Smith 2008;Chirinko and Mallick 2017). Using a substitution elasticity smaller than one will have three major implications: First, it allows studying the differential impact of factor-specific climate damages on production.…”
Section: The Numerical Modelmentioning
confidence: 99%
“…While many macro models assume a Cobb-Douglas production function, recent research based on more disaggregated data (e.g. Antras, 2004, Juselius, 2008 has shown that the elasticity of substitution between capital and labor is less than 1, i.e. ߜ < 0 in the model above.…”
Section: Discussionmentioning
confidence: 99%
“…Cobb-Douglas production function, recent research based on more disaggregated data (e.g. Antras, 2004, Juselius, 2008 has shown that the elasticity of substitution between capital and labor is less than 1, i.e. ߜ < 0 in the model above.…”
Section: Discussionmentioning
confidence: 99%